Effect of water maldistribution on cooling tower fill performance evaluation - Bertrand, Timothy Paul (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScEng (Mechanical and Mechatronic Engineering))--University of Stellenbosch, 2011.